The policy on social inclusion, valuation and environmental services of recycling in Bogota, Colombia - Tarupi Montenegro, Edisson Armando; De La Fuente De Val, Gonzalo (Cooperativismo & Desarrollo, 2016)
Introduction: The interrelations and interdependence taking place in an urban space, from the point of view of a social and ecological ecosystem, require joint and planned action in response to public policy. Methodology: Environmental economic valuation requires, first, an exploratory methodology to establish preferences of households, businesses and society in order to preserve the environmental services of recycling, and from this point of view, a description of the population or households to be chosen randomly throughout Bogota, Colombia is provided. Additionally, a Logit model is used for determining willingness to pay (wtp). Results: The contingent value survey allows to estimate the monetary value that population gives to recycling. This allows to estimate willingness to pay (wtp) for the environmental services of recycling, through a Logit model, considering social and economic variables. Conclusions: If the average estimated wtp is added, considering every home in Bogota, 2,395,244,880 million Colombian pesos would be collected, which represent an investment that translates into better income for recyclers in favor of a sustainable quality of life.
Keywords: Bogota; recycling; public policy; environmental services; economic valuation.